Emergence of tan spot disease caused by toxigenic Pyrenophora tritici-repentis in Australia is not associated with increased deployment of toxin-sensitive cultivars - Oliver, Richard; Lord, M.; Rybak, K.; Faris, J.; Solomon, P. (American Phytopathological Society, 2008)
The wheat disease tan (or yellow leaf) spot, caused by Pyrenophora tritici-repentis, was first described in the period 1934 to 1941 in Canada, India, and the United States. It was first noted in Australia in 1953 and only became a serious disease in the 1970s. The emergence of this disease has recently been linked to the acquisition by P. tritici-repentis of the ToxA gene from the wheat leaf and glume blotch pathogen, Stagonospora nodorum. ToxA encodes a host-specific toxin that interacts with the product of the wheat gene Tsn1. Interaction of ToxA with the dominant allele of Tsn1 causes host necrosis. P. tritici-repentis races lacking ToxA give minor indistinct lesions on wheat lines, whereas wheat lines expressing the recessive tsn1 are significantly less susceptible to the disease. Although the emergence and spread of tan spot had been attributed to the adoption of minimum tillage practices, we wished to test the alternative idea that the planting of Tsn1 wheat lines may have contributed to the establishment of the pathogen in Australia. To do this, wheat cultivars released in Australia from 1911 to 1986 were tested for their sensitivity to ToxA. Prior to 1941, 16% of wheat cultivars were ToxA-insensitive and hence, all other factors being equal, would be more resistant to the disease. Surprisingly, only one of the cultivars released since 1940 was ToxA insensitive, and the area planted to ToxA-insensitive cultivars varied from 0 to a maximum of only 14% in New South Wales. Thus, the majority of the cultivars were ToxA-sensitive both before and during the period of emergence and spread of the disease. We therefore conclude that the spread of P. tritici-repentis in Australia cannot be causally linked to the deployment of ToxA-sensitive cultivars.